PERANCANGAN ALAT PENCETAK PEMPEK KRITING DI UKM PEMPEK â€œBU LINAâ€ PALEMBANG - Adryanus Nikke Hertanto; Achmad Alfian (Teknoin, 2016)
Pempek "BU LINA" is one of the SMEs which make pempek kriting in Palembang. The crockery is conventional in making pempek kriting. Workers often have complaints on time makes pempek kriting, it is necessary to perform the design of an appropriate tool, with ergonomic aspects that can reduce the complaints of injury musculoskeletal occupational and also benefit from the financial point of initial phase of the study done by observing the conditions and process of making pempek kriting basis directly. After conducting measurements anthropometric data of workers in pempek "BU LINA", the obtained dimensions pempek kriting maker. The size is: 154.33 cm tall tool because the tool is placed on a table with a height of 60 cm tall appliance then be 94.33 cm, height container printout 96.33 cm, width 41 cm maximum tool, and great grip crank 3,35 cm. In addition to musculoskeletal complaints decreased by 42.18 %. And increasing output device that reaches 169% it is certain display devices is advantageous.